Environmental Audit and CSR Practices on the Financial Performance of Small and Medium Manufacturing Companies in Indonesia - Nugrahanti, Trinandari Prasetya; Lysandra, Shanti (Ilomata International Journal of Tax and Accounting, 2024)
By employing environmental audits, businesses can meticulously assess environmental risks, fortify sustainability practices, and foster enhanced stakeholder trust. Concurrently, the adoption of CSR practices emerges as a driving force behind improved financial performance, operational efficiency, and long-term sustainability. This study investigates the profound impact of environmental audit and Corporate Social Responsibility (CSR) practices on the financial performance of small and medium manufacturing companies in Indonesia. This research uses quantitative methods with primary data obtained through a questionnaire. The sample selection from the population of manufacturing companies in Indonesia was carried out purposefully. The data that has been collected will be analyzed by regression to be able to answer existing hypotheses. The results showed that environmental audits and CSR can have a positive and significant effect on their financial performance. This means that financial performance and CRS will increase along with improvements in financial performance. These findings carry substantial implications for the manufacturing sector, advocating for responsible business practices and making theoretical strides by emphasizing the integration of sustainability into financial theories and models, specifically within the context of Indonesia's industrial landscape.